2023
DOI: 10.7759/cureus.35558
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Incident Kidney Stones in Indian Adults: A Hospital-Based Cross-Sectional Study

Abstract: BackgroundThe diverse manifestations of urolithiasis provide very interesting epidemiological data. This has prompted various studies to look into the etiopathogenesis of renal stones, which is believed to be multifactorial, both exogenous and endogenous. VDR Fok1 is a risk factor for renal stone formation and could cause the formation of renal stones through the mechanism of crystal induction and crystallization in the urine. While a few recent studies have shown the role of heavy metals like cadmium and lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Other studies have identified some other risk factors, like male gender, increased age, sedentary lifestyles, and diets rich in fats, etc. [ 10 - 12 ]. However, studies on groundwater quality parameters of the stone-belt states are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified some other risk factors, like male gender, increased age, sedentary lifestyles, and diets rich in fats, etc. [ 10 - 12 ]. However, studies on groundwater quality parameters of the stone-belt states are scarce.…”
Section: Introductionmentioning
confidence: 99%